ATP-gated P2x7 receptors express at type II auditory nerves and required for efferent hearing control and noise protection - Chun Liang; Tian-Ying Zhai; Jin Chen; Shu Fang; Yan Zhu; Li-Man Liu; Ning Yu; Hong-Bo Zhao (Proceedings of the National Academy of Sciences, 2025)
Negative feedback of the cochlear efferent system plays a critical role in control of hearing sensitivity and protection from noise trauma. Type II auditory nerves (ANs) innervate outer hair cells (OHCs) in the cochlea and provide an input to the cochlear efferent system to achieve hearing sensitivity controlling and protection; in particular, medial olivocochlear efferent nerves innervate OHCs to control OHC electromotility, which is an active cochlear amplifier in mammals. However, little is known about channel information underlying type II AN activity and consequent function. Here, we report that ATP-gated P2x7 receptor had a predominant expression at type II spiral ganglion (SG) neurons and the synaptic areas under inner hair cells and OHCs with lateral and medial olivocochlear efferent nerves. Knockout (KO) of P2x7 increased hearing sensitivity with enhanced acoustic startle response, auditory brainstem response, and cochlear microphonics by increasing OHC electromotility. P2x7 KO also increased susceptibility to noise and exacerbated ribbon synapse degeneration. Middle-level noise exposure could impair active cochlear mechanics resulting in hearing loss in P2x7 KO mice. These data demonstrate that P2x7 receptors have a critical role in type II SG neuron’s function and the cochlear efferent system to control hearing sensitivity; deficiency of P2x7 receptors can impair type II SG neuron’s function and the cochlear efferent suppression leading to increase of active cochlear amplification and hearing oversensitivity, i.e., hyperacusis, and susceptibility to noise, which may also associate with other hearing disorders, such as tinnitus.